Implementasi Teknologi pada Pembelajaran Anak Usia Dini - Rohmah, Naili; Aflahani, Ari Purnomo Endah (PIAUD Universitas Islam Negeri Sunan Kudus, 2019)
Early Children Learning Optimization through Use of Technology. The purpose of this article is to get a detailed describe that using technology can optimize learning in the PAUD field. The rapid development of technology is inevitable in human life, but the existence of technology still has positive and negative impacts.. Almost all aspects of human life are accompanied by technology, including in education. Technology is needed in education in order to facilitate learning activities. The objective of technology can be use at all levels of education, including early childhood education (ECE) level. Some of the examples of technology products in our environment such asat home and school environment are: gadgets, mobile phones, televisions, refrigerators, dispensers, magic com, ovens, sewing machines, gas stoves, electricity, computers, irons, fans, and air conditioners. The transportations used includes: bicycles, motorcycles, cars, trucks, buses, trains, ships, and airplanes. The various of technological products. It can be used as an attempt to develop the moral, motor, cognitive, linguistic, art, and social aspects of the early childhood. It is expected that the use of appropriate technology can optimize learning for early childhood.